2018
DOI: 10.1002/ece3.4644
|View full text |Cite
|
Sign up to set email alerts
|

Genetic patterns in peripheral marine populations of the fusilier fish Caesio cuning within the Kuroshio Current

Abstract: AimMayr's central‐peripheral population model (CCPM) describes the marked differences between central and peripheral populations in genetic diversity, gene flow, and census size. When isolation leads to genetic divergence, these peripheral populations have high evolutionary value and can influence biogeographic patterns. In tropical marine species with pelagic larvae, powerful western‐boundary currents have great potential to shape the genetic characteristics of peripheral populations at latitudinal extremes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 81 publications
4
15
0
Order By: Relevance
“…Nucleotide diversity and F IS were lowest, and relatedness highest, in the peripheral Japanese site. These findings are congruent with the idea that edge populations are subject to higher rates of genetic drift owing to reduced N e [6,10] and match previous studies that found declining genetic diversity along the Kuroshio Current towards species' northern range margins [67]. However, our analyses also estimated similar long-term N e in all three sites and no signatures of recent bottlenecks at the range edge.…”
Section: (A) Life On the Edgesupporting
confidence: 92%
“…Nucleotide diversity and F IS were lowest, and relatedness highest, in the peripheral Japanese site. These findings are congruent with the idea that edge populations are subject to higher rates of genetic drift owing to reduced N e [6,10] and match previous studies that found declining genetic diversity along the Kuroshio Current towards species' northern range margins [67]. However, our analyses also estimated similar long-term N e in all three sites and no signatures of recent bottlenecks at the range edge.…”
Section: (A) Life On the Edgesupporting
confidence: 92%
“…To limit the influence of nonindependent loci, linkage disequilibrium (LD) was tested between all SNP pairs using the package genetics v1.3.8.1.2 (Warnes et al., 2019), and SNPs at strong linkage disequilibrium ( r 2 > 0.8) were removed (Lee et al., 2018; Tian et al., 2009). SNPs with high observed heterozygosity ( H o > 0.6) were also dropped from the dataset (e.g., Ackiss et al., 2018; Hohenlohe et al., 2010; Van Wyngaarden et al., 2017) using pegas v0.11 (Paradis, 2010), to eliminate loci exhibiting extremely high heterozygosity resulting from false SNP calls or assembly errors (Lee et al., 2018). Analyses were performed in R version 3.5.3 (R Core Team, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Altogether, this suggests that long distance dispersal in this species requires a strong oceanographic conduit. Using approximately 2,500 SNPs generated from RAD sequencing, Ackiss et al (2018) found evidence of reduced genetic diversity in the peripheral populations of this species in relation to the Kuroshio Current, a powerful western-boundary current in the Pacific Ocean. The authors found that sites closest to the periphery exhibited increased within-population relatedness and decreased effective population size, and potential for local adaptation.…”
Section: Transecting Geographic Rangesmentioning
confidence: 97%